(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2013)
We described the proximal epiphysis of a rhinoceros third metacarpus collected from the level XI of Grotta Romanelli. This level is chronologically referred to a time span between approximately 80 and 69 ka. Morphological and morphometric characters of the third metacarpus suggest that it belongs to Coelodonta antiquitatis. This is the earliest record of woolly rhino in Italy.